The Effect of Different Optical Clearing Agents on the Attenuation Coefficient and Epidermal Thickness of Human Skin Assessed by Optical Coherence Tomography - Maria Varaka; Martha Z. Vardaki; Georgios Gaitanis; Ioannis D. Bassukas; Nikolaos Kourkoumelis (Applied Sciences, 2022)
Background: Optical coherence tomography (OCT) is a non-invasive imaging technique based on the interferometry of backscattered light. However, strong light scattering hinders its applicability in clinical dermatology. The strength of scattering is exemplified by the attenuation coefficient which is the rate of OCT signal decay in depth. Attenuation can be reduced by topical application of hyperosmotic liquids with a high refractive index, namely optical clearing agents (OCAs). In this study, we assessed the impact of different OCAs to enhance skin optical permeability in OCT images. In vivo tests were carried out to determine the OCT attenuation coefficient (μOCT) and epidermal thickness in the treated and untreated epidermis. Methods: Four OCAs were studied: Propylenglycol, propylenglycol combined with oleic acid in equal proportions (1:1 v/v), Vaseline, and liquid Vaseline. Percentage change of μOCT and epidermal thickness were estimated by OCT imaging of a healthy forearm skin, prior to the application of each OCA and after the application, at two time points, t1 = 5 min, and t2 = 90 min. μOCT was quantitatively obtained by fitting the OCT signal to a single scattering model. Results: The application of OCAs induced significant changes in both μOCT (decreased) and epidermal thickness (increased). The synergistic effect of the combined propylenglycol with oleic acid reduced the μOCT by 43% while propylenglycol induced the highest increase (33%) in epidermal thickness, both at t2. Conclusions: Topical administration of propylenglycol combined with oleic acid can reduce light attenuation in OCT imaging within the clinically relevant timeframe of 90 min.